Gadolinium‐Enhancing Lesions Lead to Decreases in White Matter Tract Fractional Anisotropy in Multiple Sclerosis. Issue 3 (13th October 2015) - Chiang, Gloria C.; Pinto, Soniya; Comunale, Joseph P.; Gauthier, Susan A.
ABSTRACT: PURPOSE: Although MRI identification of new lesions forms the basis for monitoring disease progression in multiple sclerosis patients, how lesion activity relates to longitudinal white matter changes in the brain is unknown. We hypothesized that patients with gadolinium‐enhancing lesions would show greater longitudinal decline in fractional anisotropy in major tracts compared to those with stable disease. METHODS: Thirty patients with relapsing‐remitting multiple sclerosis were included in this study—13 had enhancing lesions at baseline and 17 did not. Each patient underwent at least two 3 Tesla contrast‐enhanced MRI scans with a DTI sequence with a median interval of 2.1 years between scans. The forceps major and minor of the corpus callosum and the bilateral corticospinal tracts were selected as the major white matter tracts of interest. These tracts were reconstructed using region‐of‐interest placement on standard anatomical landmarks and a fiber assignment by continuous tracking algorithm using TrackVis (version 0.5.2.2) software. Mixed‐effects regression models were used to determine the association between enhancing lesions and subsequent longitudinal change in fractional anisotropy. RESULTS: In patients with enhancing lesions, there was greater decline in fractional anisotropy compared to those with stable disease in the forceps major ( P = .026), right corticospinal tract ( P = .032), and marginally in the left corticospinal tract ( P = .050), but not the forceps minor ( P = .11). CONCLUSION: Fractional anisotropy of major white matter tracts declined more rapidly in patients with enhancing lesions, suggesting greater diffuse white matter injury with active inflammatory disease. DTI may provide a means of monitoring white matter injury following relapses.